Leachate tertiary treatment using wetlands cultivated with oilseeds - Florênço, João Antônio Monteiro; Scherolt, Lucas Zanon; Trevisan, Viviane; Skoronski, Everton (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The objective of this study was to evaluate the efficiency of the wetlands cultivated with sunflower and soybean in the removal of Chemical Oxygen Demand, ammonia, nitrate, nitrite, total phosphorus and Kjeldahl Total Nitrogen (KTN) of the treated leachate from the landfill treatment plant of the city of Lages / SC. It was also analyzed the plants development as a function of the effluent applied in the wetlands compared to wetlands irrigated with chemical fertilizer. The wetlands were operated in batch with hydraulic retention times (HRT) of 2 and 4 days, receiving treated slurry in concentrations of 10 and 25% and liquid chemical fertilizer (5 ml / L). In the tests carried out with HRT of 4 days only the concentrations of COD and of ammonia were analyzed. After 4 months, the plants size was measured to verify their growth. In the tests carried out with the soybean there was no germination of the seeds. In both HRT tested, a greater removal of phosphorus, ammonia, nitrite and KTN was observed when 25% concentration of leachate. It was observed that the sunflower plants showed a higher size when cultivated in wetlands operated with HRT of 4 days and that they received the treated leachate in the concentration of 10%.